Respuesta :

Answer:

(1): "*-5x2y" was replaced by "*(-5x2y)".

(2): "x2"   was replaced by   "x^2".  1 more similar replacement(s).

STEP

1

:

Equation at the end of step 1

 (3x • (y2)) • (0 -  (5x2 • y))

STEP

2

:

Equation at the end of step

2

:

 3xy2 •  -5x2y

STEP

3

:

Multiplying exponential expressions :

3.1    x1 multiplied by x2 = x(1 + 2) = x3

Multiplying exponential expressions :

3.2    y2 multiplied by y1 = y(2 + 1) = y3

I believe the answer is   ( -3•5x3y3)

ACCESS MORE